(untitled) (Journal of Philosophy Culture and Political Science, 2022)
After gaining independence, Kazakhstan began to reorganize its official historiography, which contributed to the formation of a new national state. Kazakhstan, like other post-Soviet countries, has taken up the issue of nationalization of the territory or the formation of a national territory during the years of independence after strengthening its statehood, it is known that the ruling elite chose civic identity as a guarantee of social and political Society. According to domestic and foreign researchers, civil and ethnic identity in Kazakhstan is used in parallel in the construction of the nation. The article analyzes what direction Kazakhstan chose in the first years of independence against the background of this identity. The study describes the evidence that Kazakhs are the main ethnic nation that forms the state, attempts to legalize the existence of the Kazakh ethnic group on the land of Kazakhstan from time immemorial, the use of the history and symbol of the Kazakh ethnic group as a state-forming nation. The reasons for choosing this ethno-cultural center in the first year of independence will be discussed. The methodology of the study was the study of the works of domestic and foreign researchers, comparative analysis of history textbooks, national state documents, and programs. As a result of the study, it was noted that in the first year of independence, Kazakhstan pursued an ethno-oriented policy. This policy is reflected in the fact that the Kazakh ethnic group has been a people living in this region since ancient times, and the main goal of the national policy pursued by the country’s political leadership since the first days of independence is to maintain a balance between ethnic and civic identity. It seemed that the main direction of nation-building was directly transferred to the state, the ruling political elite. Since the adoption of the new Constitution, it has been noted that the issues of forming the civil and ethnic identity of society have been identified in the construction of the nation. The results obtained as a result of the work contribute to the writing of scientific papers related to nation-building in Kazakhstan and its further study. Keywords: nation-building, historiography, symbol,ethnos,identity